Microsomal epoxide hydrolase genotype and risk of myocardial infarction - Cornelis, Marilyn C. (2007)
DNA damage caused by mutagens found in tobacco smoke may contribute to the development of coronary heart disease (CHD). Microsomal epoxide hydrolase (EPHX1) is involved in the metabolism of tobacco smoke mutagens and an amino acid substitution (H139R) in exon 4 of the EPHX1 gene is associated with increased enzyme activity. The objective of this study was to investigate the effect of EPHX1 genotype on risk of myocardial infarction (MI) and to determine whether smoking interacts with genotype to modify risk. Cases (n = 2,022) with a first acute non-fatal MI and population-based controls (n = 2,022) living in Costa Rica, matched for age, sex and area of residence were genotyped by RFLP-PCR. Smoking status was determined by questionnaire. The frequency of the R139 allele was 17% for both cases and controls. EPHX1 genotype was not associated with risk of MI, regardless of smoking status. Compared to individuals with the HH genotype, the multivariate adjusted odds ratio (95% confidence interval) for risk of MI was 0.95 (0.81–1.11) for individuals with the HR genotype and 1.18 (0.79–1.76) for those with the RR genotype. These results suggest that EPHX1 does not play a significant role in the development of CHD.